ANALISIS PENAWARAN TANDAN BUAH SEGAR DI PROVINSI RIAU - Ermi Tety; Helentina Situmorang (PEKBIS, 2012)
The purpose of this research is to find out the factors of supply palm oil in Provinceof Riau and the effects of fluctuate its factors of supply palm oil. This research did inPekanbaru on January 2008 until September 2008 to analyze about Riau’sproblems. Research method is the study of literatures in secondary data 1987-2006analyzed by SAS 6.12 programme and WinQSB software. The factors of supplypalm oil in Province of Riau are real price of CPO, real price of urea, wide of palm oilplantations, productivities of palm oil.This research get F value =2.283,68 in probability α=1%, R-square 0,9984 to showthat correlation independent between dependent are strong, Adj R-square 0,9979 toshow that 99,79 % independent explanated by dependent. But, 0,22 % explanatedby other factors that not included. Real price of CPO, wide of palm oil plantationsand productivities palm oil show positive’s effect relevan with eaches estimated on2,10 (probability α=16 %), 3,46 (probability α=1%), and 223.471 (probability α=1%).Real price of urea shows negative’s effect relevan with estimated on -52,62(probability α=1%). The result forecasting analysis with SEST (Single EksponensialSmoothing With Trend Linier) with estimation, in 2011 real price of CPO is Rp.62.103,24/ton, real price of urea is Rp. 41.355,78/ton and wide of palm oilplantations is 1.758.169,00 ha.